Between Subway and Spaceship: Practical Ethics at the Outset of the Twenty-first Century - Benjamin, Martin (The Hastings Center report, 2001)
Moral deliberation involves a constant interplay among specific judgments, general moral values and principles, and background beliefs about the world. We may also construct broad moral theories to explain how our judgments and general commitments hang together, but there is little hope of settling on any one comprehensive moral theory.